Religious fundamentalism and political extremism - Weinberg, Leonard, 1939-; Pedahzur, Ami. (London ; Portland, OR : Frank Cass, 2004)
This volume explores the relationships between fundamentalist religious belief, political extremism and outbreaks of religiously inspired violence.
The return of martyrdom : honour, death, and immortality / Benjamin Beit-Hallahmi -- Two religious meaning systems, one political belief system : religiosity, alternative religiosity, and political extremism / Daphna Canetti-Nisim -- Religious violence and the myth of fundamentalism / Michael Barkun -- The uniqueness of Islamic fundamentalism and the fourth wave of international terrorism / Gabriel Ben-Dor and Ami Pedahzur -- Jewish self-defence and terrorist groups prior to the establishment of the State of Israel : roots and traditions / Arie Perliger and Leonard Weinberg -- Counting the causes and dynamics of ethnoreligious violence / Jonathan Fox -- Reflections on fascism and religion / Roger Eatwell.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050
Keywords: Religious fundamentalism; Radicalism; Religion and politics; Violence -- Religious aspects; Terrorism -- Religious aspects; POLITICAL SCIENCE -- Political Ideologies -- General; Radicalism; Religion and politics; Religious fundamentalism; Terrorism -- Religious aspects; Violence -- Religious aspects; Electronic books